2020
DOI: 10.1038/s41598-020-62346-8
|View full text |Cite
|
Sign up to set email alerts
|

Study on collagen parameters in vulvar cancer and preneoplastic lesions by Second Harmonic Generation microscopy

Abstract: were plotted as the median and interquartile range (25th-75th). The Mann-Whitney nonparametric test was used to analyze numerical variables between two groups. The Kruskal-Wallis test was used to analyze numerical variables between three groups. Data analysis was performed using GraphPad Prism v 8.0 software (GraphPad Software, San Diego, CA). All comparisons were considered statistically significant at p < 0.05.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Kalliopi 5 systematically investigated the expression profile of VSCC for the first time using the microarray technology and delineated the molecular parameters to reveal the cellular pathways involved in the pathogenesis of VSCC. Recently, second harmonic generation (SHG) microscopy has been used for the analysis of collagen fibers in VSCC and preneoplastic lesions and an evident decrease in the values of collagen fiber parameters in the VSCC was discovered by Leuridan et al 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalliopi 5 systematically investigated the expression profile of VSCC for the first time using the microarray technology and delineated the molecular parameters to reveal the cellular pathways involved in the pathogenesis of VSCC. Recently, second harmonic generation (SHG) microscopy has been used for the analysis of collagen fibers in VSCC and preneoplastic lesions and an evident decrease in the values of collagen fiber parameters in the VSCC was discovered by Leuridan et al 19 …”
Section: Discussionmentioning
confidence: 99%
“…Kalliopi 5 systematically investigated the expression profile of VSCC for the first time using the microarray technology and delineated the molecular parameters to reveal the cellular pathways involved in the pathogenesis of VSCC. Recently, second harmonic generation (SHG) microscopy has been used for the analysis of collagen fibers in VSCC and preneoplastic lesions and an evident decrease in the values of collagen fiber parameters in the VSCC was discovered by Leuridan et al 19 Previous research, 6 which mainly focused on genomic aberration patterns and expression profiles of VSCC, illustrated a concordant relationship between the imbalances scored by aCGH and the level of gene expression found by microarray. Genes located in gained regions were generally overexpressed while those located in lost regions were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that organization, uniformity and quantity, of collagen fibers were reduced in both preneoplastic lesions and squamous carcinoma as compared to normal tissue, Though, the difference between preneoplastic lesions and squamous carcinoma was not notable. On the other hand, the presence of distant metastasis correlated with increased collagen uniformity and quantity compared to VSCC without metastasis [81]. SH microscopy can identify three tumor-associated collagen signatures (TACS) at different stages of tumor progression.…”
Section: Applications For Cancer Imagingmentioning
confidence: 99%
“…Collagen quantity, uniformity and organization measured with SHG and ImageJ software in both the forward and backwards directions can identify human mammary tumor subgroups [57] and collagen quantity and uniformity from SHG images can predict outcome in luminal breast cancer [58]. Similarly in human vulvar squamous cell carcinoma, increased collagen quantity and uniformity correlated with the presence of distant metastasis, suggesting that these collagen parameters could be used for prognosis in this type of cancer as well [59]. In murine colorectal cancer, SHG paired with metabolic in vivo imaging could predict response to chemotherapy [60], which could tailor personalized oncologic therapies.…”
Section: Plos Onementioning
confidence: 99%